AGN Variability in the UKIDSS Ultra Deep Survey - Elmer, Elizabeth (2021)
One of the defining characteristics of Active Galactic Nuclei (AGN) is the variations observed in their fluxes. In this thesis, we present the first attempt to select AGN using long-term near-infrared (NIR) variability. By analysing the K-band light curves of all the galaxies in the UKIDSS Ultra Deep Survey (UDS), the deepest NIR survey over ~1 sq degree, we have isolated 393 variable AGN candidates. In order to minimise any contamination, known galactic stars were removed from the catalogue before the selection was run, and we took care to suppress any spurious variations due to atmospheric seeing. A comparison to other selection techniques shows that only half of the variable sources are also selected using either deep Chandra X-ray imaging or IRAC colour selection, suggesting that using NIR variability can locate AGN that are missed by more standard selection techniques. In particular, we find that long-term K-band variability identifies AGN at low luminosities and in host galaxies with low stellar masses, many of which appear relatively X-ray quiet.